RELATION BETWEEN THE SOCIAL SUPPORT AND MOTHERS’ PARENTING STRESS WITH CHILDREN IN PRIMARY SCHOOLS DURING THE COVID-19 PANDEMIC - Kartiko, Lubnaa Sulistiyani; Saharuddin; Andi Tihardimanto; Nadya Haruna; Mukhtar Lutfi (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
The Covid-19 pandemic was considered to be the major cause of mothers’ stress in educating their children. Parents have to face a pandemic situation with a new policy of quarantine and School from Home (SFH) which is significantly related to parental stress. This study aims to investigate relation between the sosial support and mothers’ parenting stress with children in primary schools during the Covid-19 pandemic. A quantitative study with a cross sectional research design was adopted in this study. The population of this study were all mothers totaling 300 people. The purposive sampling technique was employed in selecting the research samples. The samples of this research consisted 171 mothers of student from primary schools. The instruments used in this research were the demographic questionnaire, the sosial support questionnaire, and the parenting stress index questionnaire. The obtained data were processed and analyzed using the Chi Square test. The findings of this research indicated that the sosial support significantly influenced the mothers’ level of stress with the children studying in primary school.